Ramsay Hunt syndrome in a young COVID-19 patient - Claudia P Alonzo-Correa (Wolters Kluwer Medknow Publications, 2021)
The severe acute respiratory syndrome caused by coronavirus-2 can present with a broad spectrum of clinical manifestations, mainly respiratory, but also with different neurologic symptoms. On the other hand, the Ramsay Hunt syndrome (RHS) is a complication of varicella-zoster virus (VZV) reactivation presenting mainly in older patients, patients under stress, infection, or an immunocompromised state. We report a case of RHS in a young Mexican female patient who tested positive for SARS-CoV-2 in whom we believe that there is a strong possibility that VZV's unusual reactivation, presenting as RHS in a young patient, might have been a consequence of the immunological alterations induced by this coronavirus.